Anti-inflammatory Activity of Water Extract of Luvunga sarmentosa (BI.) Kurz Stem in the Animal Models - Sabar Deyulita; Hilkatul Ilmi; Hanifah Khairun Nisa; Lidya Tumewu; Aty Widyawaruyanti; Achmad Fuad Hafid (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The study was aimed to determine the anti-inflammatory activity of water extract of the Luvunga sarmentosa stem in an animal model. Twenty-five Wistar rats were divided into five groups (n=5). Group 1 was administered 0.9% normal saline (negative control), group 2 was administered 150 mg/kg diclofenac sodium (positive control), and groups 3 to 5 were administered 50, 300, and 550 mg/kg BW of L. sarmentosa extract, respectively. Carrageenan was injected subcutaneously into each rat's subplantar region of the left hind paw. The paw volume was measured using a plethysmometer. The results showed that the water extract of L. sarmentosa stem (doses of 50, 300, and 550 mg/kg BW) significantly reduced the paw edema volume from the 4th to 5th hour compared to the negative control. The percent inhibition of edema at the 5th hour is 47.45; 46.95; 50.39%. The first phase of the edema (1st and 2nd hour) was not affected by the extract. Meanwhile, diclofenac sodium decreased paw edema volume from the 1st to 5th hour with a percent inhibition of 95.90% at the 5th hour. The histopathology result is relevant to the percentage inhibition of edema. Treatment with L. sarmentosa extract showed slight improvement, destruction of epidermal tissue, hyperkeratotic skin, and subepidermal edema. Meanwhile, positive control showed no inflammatory signs with normal keratin, subepidermal, and subcutaneous layers. The water extract of L. sarmentosa stem has anti-inflammatory activity. This extract effectively reduces the paw edema volume in the late phase with decreased neutrophil infiltration.